KARAKTERISASI SUBSTRAT DAN SUHU EKSTRAK KASAR LIPASE Aspergillus niger M1407 - Amelia M Salmon; Mellissa E. S. Ledo; Merpiseldin Nitsae (Fakultas Pertanian, Universitas Timor, 2020)
Isolation of crude extract lipase Aspergillus niger M1407 using kesambi seeds flour medium through solid state fermentation was carried for substrate and temperature characterization fo determenie optimal condition enzyme substarate reaction. The aim of this study are determenie the substrate and temperature profile crude extract lipase Aspergillus niger M1407. This research was conducted in the laboratory (microbiology and chemistry) of the Biology Education Study Program at Artha Wacana Christian University, Kupang, in January 2019 untel March 2019. The method used in this study divided into four stages, namely medium preparation for Aspergillus niger M1407 lipase; Solid-State Fermentation medium for 7 days; substrate characterization using oleic acid + ethanol in isooktan and oleic acid + methanol in isooktan and temperature characterization was done at 20oC, 30oC, 40oC, 50oC, and 60oC. Analysis of crude extract lipase Aspergillus niger M1407 activity using the titration method. Data obtained in quantitative descriptive analysis. The results of this study indicate that the crude extract lipase Aspergillus niger M1407. crude enzyme lipase Aspergillus niger M1407 activity is better on oleic acid methanol + substrate which has 200 U / mL activity while temperature characterization show best activity at 40oC with 580 u / mL lipase activity.